Reward meritocracy or nepotism: The case of independent financial advisors appointed by Chinese listed companies - Cen Wu; Qingquan Tang (China Journal of Accounting Research, 2019)
As independent financial advisors, securities firms are the core intermediaries in major asset reorganization (MAR) of listed companies. Furthermore, they play the dual roles of transaction and authentication. Based on this institutional background, this paper studies how listed companies choose between industry experience ("meritocracy") and relationships ("nepotism"). Using the MAR of A-share listed companies from 2008 to 2013 as the sample, this paper shows that higher transaction costs (i.e., greater demand for the transaction function of advisors) are related to the higher possibility of advisors with weaker relationships and more industry experience being hired. It also shows that higher suspicion of tunneling (i.e., greater demand for the signal of fairness associated with advisors' authentication function) is related to the higher possibility of advisors with weaker relationships being hired, but it is not significantly related to whether advisors have more or less industry experience. This paper also shows that reputation has a certain governance effect on the negative consequences of relationship. For the most part, listed companies reward meritocracy but not nepotism when appointing independent financial advisors.
Keywords: 650; Authentication role; Independent financial advisors; Industry experience; Relationship; Transaction role